Avaliação in vitro da rugosidade de superfície de uma resina composta coberta com selantes com ou sem carga quando submetida à abrasão por escovação com diferentes tipos de dentifrícios - Pressi , Heloísa (2015)
The objectives of this in vitro study were: 1) to evaluate the surface roughness of a composite resin covered by sealing surface containing inorganic filler or not, subject to brushing; 2) to analyze, with the aid of scanning electron microscopy, the presence of the sealant after 48 months of simulated toothbrushing; 3) verify that the type of toothpaste reduces the useful life of sealants; 4) verify the presence of inorganic filler prevents the increase in roughness forward to brushing. For this, 54 samples were made of composite resin and divided into nine groups: G1 - without composite sealant (control); G2 - Sealant Fortify, toothpaste Colgate Professional Whitening; G3 - Fortify, Colgate Total Clean Mint; G4 - Fortify, Edel White Whitening; G5 - Fortify, Edel White Gum Care; G6 - Fortify Plus, Colgate Whitening Professional; G7 - Fortify Plus, Colgate Total Clean Mint; G8 - Fortify Plus White Whitening Edel; G9 - Fortify Plus, Edel White Gum Care and analyzed the simulated periods of brushing (12,24, 36 and 48 months). Reading roughness was performed at baseline and after each simulated toothbrushing period, using a surface roughness (SJ 201 Mututoyo).Two specimens of each group were observed by SEM. The data were submitted to ANOVA and Tukey's test (5%). There was a significant difference between the two sealants, with the sealant Fortify Plus rougher. Among the toothpaste, Colgate Clean Mint associated with Fortify Plus sealant obtained the higher roughness values. Lower values were associated with Gum Care Fortify sealant. The protective layer formed by the sealant remained partially by the end of 48 months of brushing, maintaining the smoothness of the composite. We conclude that both sealants guaranteed protection of the composite, and the Fortify Plus rougher for all assessed toothpastes. Clinical significance: The roughness of the surface sealant is changed for different toothpastes and different times of brushing and the addition of inorganic filler in sealants promotes different performances in relation to surface roughness.